Sie sind auf Seite 1von 12

Ψ(x, t) = Ae λ|x| e iωt ,

A, λ, ω > 0

Ψ

x x 2

x |Ψ| 2 x ( x + ∆x) ( x x)

1 = ˆ |Ψ| 2 dx = 2|A| 2 ˆ

0

e 2λx = 2|A| 2 e 2λx

2λ

= |A| 2
=⇒
A = √ λ
λ
0

x = ˆ x|Ψ| 2 dx = |A| 2 ˆ

−∞

xe 2λ|x| dx

=

x 2 = 2|A| 2 ˆ x 2 e 2λx dx = 2λ

0

(2λ) 3 =

2

1
2λ 2 .

1
1
∆x =
2λ 2 =⇒

(∆x) 2 = x 2 x 2 =

|Ψ(±x)| 2 = |A| 2 e 2λx = λe 2λ/ 2λ = λe 2 0.2431λ

±x

2|A| 2 ˆ

x

|Ψ| 2 dx = 2|A| 2 ˆ

e 2λx dx = 2λ e 2λ 2λx

= e 2λx =

x

e 2 = 0.2431.

{|0 , |1 , |2 ,

n|m = δ nm

}

n! |n

α a

a |n n |n 1 n 1

a |0 0

C |Ψ α

|Ψ α a

|Ψ α |Ψ β α

= β

|Ψ α C

n=0

α

n

1 = Ψ α |Ψ α = |C| 2

∞ ∞

n=0 m=0

(α ∗ ) n
α m
n!
m!
n|m = |C| 2

=δ nm

n=0

(|α| 2 ) n

n! = |C| 2 e |α| 2 =

C = e −|α| 2 /2

a |Ψ α = C

n=0

n

α

n! a

|n

n|n1

= C

n=1

n
α

n! n |n 1 = αC

n1

n=1

α

n! n |n 1 = α |Ψ α

Ψ α |Ψ β = e −|α| 2 /2 e −|β| 2 /2

∞ ∞

n=0 m=0

(α ) n

n!

m! = e (|α| 2 +|β| 2 )/2 e α β

β

m

= 0

ˆ

H

= (|1 1| − |2 2| + |1 2| |2 1|)

|1 |2

H

ˆ

ˆ

H

ˆ

H

 ˆ H |1 = (|1 + |2 ) ˆ H |2 = (|1 − |2 ).

ˆ

H

= 1

1

1 .

1

ˆ

ˆ

H v = λ v det ( H λI) = 0

λ 1,2 = ± 2

v 1 =

1

21

1

v 2 =

1

2+1

1

C 2 |+ , |−

S x (|+ −| + |− +|)

2

S y i (− |+ −| + |− +|)

2

S z (|+ +| − |− −|)

2

|+ |− S z

[S x , S y ] = i S z

S x S y |+

S z |+ = (|+ +|+ − |− −|+ ) = |+

2

2

=1

=0

S z |− = (|+ +|−

2

=0

− |− −|− ) = |−

2

=1

[S x , S y ] = S x S y S y S x = 2

4

0

1

2

4

i

0

i i

0

0

0

i

1 0

0

i

i 0

0

i

i 0

1

0

= i

2

1

0

1 0 = i S z

0 =

1

S x S y

1

2 | [S x , S y ] |+ | =

b)

2

| +|S z |+ | = 2 +| |+ +|−|− −| |+ = 2

4

4 .

S x S y

a A Ψ

a = a Ψ, Ψ = Ψ, aΨ = Ψ, AΨ = Ψ, A Ψ = AΨ, Ψ = aΨ, Ψ = a Ψ, Ψ = a

a

b B Ψ

b = b Ψ, Ψ = Ψ, BΨ = Ψ, B Ψ = BΨ, Ψ = bΨ, Ψ = b Ψ, Ψ = b

b

λ, µ A v, u

(λ µ) v, u = λ v, u

µ v, u = λv, u v, µu

= Av, u v, Au = v, A u v, Au = v, (A A)u = 0

λ µ

= 0 λ|µ = 0

[p, x n ] = i nx n1

[p, F (x)] = i F

∂x

F

n = 1

n 1 n n 1

[p, x n ] = [p, x·x n1 ] = x

[p, x n1 ]

=i (n1)x n2

+ [p, x] x n1 = x·(i (n1)x n2 )i x n1 =

=i

= i nx n1

n

F (x) = a n x n

∞ ∞

[p, F (x)] =

n=0

a n [p, x n ] =

a)

n=1

a n (i nx n1 ) = i

n=1

a n nx n1 = i F ∂x

A B

i[B, A] Ψ = 2 AΨ, BΨ

i[B, A] Ψ = i Ψ, BAΨ i Ψ, ABΨ

A,B i BΨ, AΨ i AΨ, BΨ

=

=

i AΨ, BΨ i AΨ, BΨ = i AΨ, BΨ AΨ, BΨ

= 2i AΨ, BΨ

= 2 AΨ, BΨ

A B [A, B] = 0 A Ψ i a i

A

ABΨ i AB=BA BAΨ i = Ba i Ψ = a i BΨ i

=

BΨ i a i A BΨ i Ψ i b i BΨ i = b i Ψ i Ψ i B

BΨ i a i B

a i B

A

n=0

A n

e A+B = e A e B [A, B] = 0

e A e A = e A e A = 1

[A, [A, B]] = [B, [A, B]] = 0

e A Be A .

f(λ) = e λA Be λA

[A, [A, B]] = [B, [A, B]] = 0

e B e A = e A e B e [B,A]

e A

n!

e A+B =

n=0

1

n! (A + B) n

=

AB=BA

n=0

1

n!

n

k=0

=

n=0

A

n

n!

n=0

B n

n!

= e A e B

e A e A = e A+A = e 0 = 1

n

k

A k B nk =

n

k

A

B nk

n=0

k=0

k!

(n k)!

e A e A = e AA = e 0 = 1

f

(λ)

f

(λ)

=

e λA ABe λA + e λA B(A)e λA = e λA [A, B]e λA

e λA [A, [A, B]]

=

=0

e λA = 0

0 λ f (λ)

f (λ) = f (0) + λf (0) = B + λ[A, B].

λ = 1

e A Be A = B + [A, B].

f (λ) λ = 1

e A Be A = B [A, B] = B + [B, A]

S e A S 1 = e A

SBS 1 = B + [B, A].

e SBS 1 = Se B S 1 = e A e B e A

e A e B e A = e B e [B,A]

e B+[B,A] = e B e [B,A] .

e B e A = e A e B e [B,A]

.

A a 1 , a 2 , a 3 ,

|1 , |2 , |3 ,

(A a n )

n

n

(A a n )

|k A 0 A a k |k |x |x = n=1 c n |n |x

 A ψ 1 ψ 2 a 1 a 2 B φ 1 φ 2 b 1 b 2 ψ 1 = (3φ 1 + 4φ 2 )/5, ψ 2 = (4φ 1 − 3φ 2 )/5 A a 1 B B A a 1

ψ 1

ψ 1 = (3φ 1 +4φ 2 )/5 B B b 1 3 2 b 2

5

4

5

2

B A

φ 1 = (3ψ 1 + 4ψ 2 )/5,

φ 2 = (4ψ 1 3ψ 2 )/5.

φ 1 a 1 3 2 φ 2 a 1 4 2

3 2 φ 1 4 2 φ 2 a 1

5

5

5

5

3

5

2 3

5

2 + 4

5

2 4

5

2 = 337 625 .

=

pˆ 2 /2m + V ( r) r

V ( r)

ˆ

ˆ

H

ˆ

p

A rˆ

pˆ rˆ p, rˆ] = i V r) rˆ

ˆ

d

dt rˆ =

=

i

[

i

H, rˆ] + rˆ

∂t

ˆ

2

2m pˆ + V r), rˆ

= 2m pˆ[ˆp, xˆ] + [ˆp, xˆ]ˆp = pˆ

i

m

ˆ

A = pˆ

d

dt pˆ =

=

i

[

i

H, pˆ] + pˆ

ˆ

∂t

pˆ 2

2m + V r), pˆ

V r) pˆ pˆ = i

dt d pˆ =

=

i

V r),

i

= V r), = V r) = Fr)

d

2

m · dt 2 rˆ = m ·

dt pˆ

d

m

= Fr) ,

rˆ pˆ Fr) = F ( rˆ )

|ψ 0

ˆ

U t

ˆ

U t

ˆ

H U t

ˆ

U t |ψ 0

t 0 = 0 t

ˆ

ˆ

|ψ(t) = U t |ψ 0 .

i

d

dt

U t |ψ 0

ˆ

ˆ

!

=

H U t |ψ 0 .

ˆ

ˆ

U t

|ψ 0

i

d

dt

ˆ

ˆ

ˆ

ˆ

U t = H U t .

ˆ

U t t 0 = 0

∂t

ˆ

U 0

=

H = 0

ˆ

U t = e i

ˆ

H·t/ ,

1 = ψ(t)|ψ(t) = ψ(t)| U

t

!

ˆ

ˆ

U t |ψ(t)

H

ˆ

U

t

ˆ

U t

=

ˆ

e i

ˆ

H·t/